Preventive Health Behaviors Associated with Recurrent Acute Respiratory Infections: A Case-Based Epidemiological Study - Elman Boy; Doli Naufal Ritonga; Muhammad Idlal Yusriyyah Girsang; Aria Adhaini Malau (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2026)
Recurrent acute respiratory infections (ARI) in adults continue to pose a significant public health burden, particularly in communities where adherence to preventive behaviors is inconsistent. This study aimed to examine the association between preventive health behaviors and recurrent ARI using a case-based epidemiological approach. A cross-sectional analysis was conducted among 106 adults diagnosed with ARI, and data were collected using a structured questionnaire adapted from PHBS indicators assessing hand hygiene, respiratory etiquette, mask use during illness, smoking inside the home, physical distancing when symptomatic, and healthcare-seeking practices. Recurrent ARI was defined as three or more episodes within the previous 12 months, and associations were analyzed using the Chi-Square test with a significance level of p < 0.05. Several preventive behaviors, including inadequate hand hygiene, poor respiratory etiquette, limited mask use, and delayed medical consultation, showed significant relationships with recurrent ARI, with inconsistent behaviors markedly elevating recurrence risk. These findings suggest that strengthening behavior-focused health education in primary care, particularly hygiene promotion, responsible respiratory practices, mask use during illness, and timely care-seeking, may help reduce recurrent ARI among adults.